(3eHGOF Yde GdEMUGA hGdWQb GdEMUGFjIs - (3SYO MSjf(B, (3aJM Gddgs ((3YeGf(B:s (3GdCcGOjejI ddfTQ(B,s, 1999)
(3HYV GdeaGgje GdCSGSjI(B- (3JQJjH hYQV GdHjGfGJ(B- (3ebGjjS GdfRYI GdeQcRjI(B- (3ebGjjS GdJTJJ(B- (3ebGjjS Tcd GdJhRjY(B- (3eHGOF fXQjI GdEMJeGdGJ(B- (3GdeJZjQGJ GdYThGFjI hGdJhRjYGJ GdEMJeGdjI(B- (3GdJhRjYGJ GdEMJeGdjI GdeJUdI(B- (3GdEQJHGW hGdEfMOGQ(B- (3GdSdGSd GdRefjI(B- (3GdCQbGe GdbjGSjIs
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdWQb GdEMUGFjIs